Study of Dielectric Properties of Nanocrystalline Cobalt Ferrite Upto Microwave Frequencies. Issue 1 (November 2015) - Sharma, Jyoti; Parashar, Jyoti; Saxena, V.K.; Bhatnagar, D.; Sharma, K.B.
Summary: The dielectric properties of cobalt ferrite, prepared by sol‐gel auto combustion technique, were studied from low frequencies to microwave frequencies. The single phase cubic spinel structure has been confirmed by using X‐ray diffraction (XRD). The dielectric properties of the sample were studied in the low frequency range from 100 Hz to 120 MHz as well as in the high frequency range from 3.95 GHz to 5.85 GHz at room temperature. The dielectric dispersion observed at lower frequency region is due to Maxwell–Wagner two layer model, which is in agreement with Koops phenomenological theory. There is a strong co‐relation between the conduction mechanism and the dielectric behaviour of ferrites. The dielectric constant remains almost constant at microwave frequencies due to the fact that it is contributed by atomic and electronic polarization. The dielectric loss tangent shows two dielectric loss peaks at about 4.332 GHz and 4.525 GHz frequencies.